Implementasi Pembelajaran STEAM Berbasis PjBL Terhadap Kemampuan Problem Solving pada Materi Energi Alternatif di SD - Enggar Kusuma Triprani; Nawang Sulistyani; Dian Fitri Nur Aini (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2023)
The students’ problem solving abilities in science about the alternative energy resulted in a low level. A few of the causes were the teacher-centered method and the lack of students' creativity development opportunity in the learning process. This study aims to determine the effect of applying the STEAM approach using the Project-based Learning (PjBL) learning model to aid the students' problem solving abilities about the alternative energy material. This type of research is a quantitative experiment with a quasi-experimental design. The research was conducted at Ngaglik 1 Batu Elementary School in the even semester of the 2022/2023 academic year. The population was grade 5 students, and the samples were taken with purposive sampling technique. There were 28 students in the control class and 29 students in the experimental class. The data was collected using the pretest and posttest instruments. The pretest and posttest results were analyzed by parametric inferential statistics based on the prerequisite tests. The normality test used the Shapiro-Wilk and the homogeneity was tesedt using the Levene Statistics. The Independent Sample t-test was used to analyze the research problem and obtained Sig. (2 tailed) of 0.000, which meant that there was a significant difference in the posttest data in the control and experimental classes, so that the application of STEAM-PjBL learning model is concluded to be able to improve students' problem solving abilities.